A comparison of electronic cigarette smokers among urban and rural Malaysia - Md Haris Robson, Noor Zurani; Nik Mohamed, Mohamad Haniki; Ab Rahman, Jamalludin; Draman, Samsul; Kartiwi, Mira; Wee, Lei Hum; Chan, Caryn Mei Hsien; Ho, Bee Kiau; Lim, Kuang Hock; Tee, Guat Hiong; Ling, Miaw Yn (Malaysia Medical Association, 2017)
Introduction: The increasing popularity of electronic cigarettes (ECV) in Malaysia, has made it important to find out its pattern of use. The objective of this study was to determine the pattern of ECV use among urban and rural ECV users in Malaysia. Methods: A household population survey was designed to represent Malaysian adults >18 years old by urbanity at national level. A multistage stratified cluster random sampling with probabilities proportional to size (PPS), stratified by state and by urban/rural areas was done. Respondents were from six zones (North, Central, South, East, Sabah and Sarawak) who answered the NECS Questionnaire Survey Form on demographics and characteristics of ECV use. Results: A total of 4,288 individuals (72% urban) were recruited. Majority were 25-44 years old (44%), Malay (73%), Muslim (79%), married (68%) and educated to secondary education (69%). Majority (86.5%) of current ECV users started ECV use at age) =19 years old. The main reason to use ECV was to experiment (47.0%), to quit tobacco cigarette smoking (16.2%), to reduce tobacco cigarette consumption (9.6%), to reduce the cost of smoking (7.3%), and to replace tobacco smoking (5.4%). Most of the current ECV users preferred third generation devices or mechanical mods (71.9%). Overall, 55.2% of current ECV users shared their ECV liquid among friends, 48.3% obtained ECV liquid from vape shops, 7.7% from online sources, 6.0% from kiosks at shopping centres, and 2.8% from night markets. Chi Square test indicated that the only significant different predictor between urban and rural ECV users was age (p=0.03). Discussion: The majority of ECV users are young Malay Muslim males who preferred third generation devices and obtained ECV liquid from vape shops. Predictors of ECV use is important when planning public health policy for the prevention of further and future ECV use.